Anies Rasyid Baswedan Islamic Political Communication - Ainur Rahman; Adinda; Dicky Erlangga; Rahmawan Hidayatullah; Akhmad Rifa’i (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Elections are a place to find and choose leaders who are honest, trustworthy and have good quality and integrity, able to provide equitable prosperity to the community. But people as voters are often wrong in choosing leaders, voters choose not really based on good comparison and knowledge of their potential leaders. So that mistakes in choosing the ideal leader often occur in the election process. Islamic political communication becomes important to be a bridge in educating politics for the public or voters, this is all done by candidates or party political actors by actively educating the importance of choosing a quality leader for the welfare of the community. The purpose of this research is to know about the messages of Islamic political communication Anies Rasyid Baswedan which are conveyed to voters in choosing a leader. Two important points conveyed by Anies Rasyid Baswedan. That is how to choose based on a track record then compare between candidate candidates, both see the vision and mission of each candidate. This research method uses Content Analysis with a qualitative approach that explains a message of Islamic political communication Anies Rasyid Baswedan in a video titled How to Choose a Leader? On Anies Baswedan's You Tube Account.